PENGARUH UKURAN PEMERINTAH DAERAH, PAD, LEVERAGE, DANA PERIMBANGAN DAN UKURAN LEGISLATIF TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH (Studi pada Kab/Kota Pulau Sumatra) - Sari, Indah Puspa; Agusti, Restu; ', Rofika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine the effect of size of local government, local revenue, leverage, fund balance, and legislative size of the financial performance of regencie/municipalities in Sumatra Island. The population in this study are all regencie/municipalities in Sumatra Island. This study uses purposive sampling method. This research uses a sample 57 regencie/municipalities.The data of this study using secondary data in website www.djpk.depkeu.go.id.This study uses multiple linear regression analysis.The result of this study indicated that the size of local government, local revenue and fund balance are factors that effect the financial performance of local government. Leverage and legislative size had no effect on financial performance of local government.Keyword: Financial performance, local government, local revenue, fund balance and legislativesize